1972
DOI: 10.1002/1097-0142(197205)29:5<1387::aid-cncr2820290541>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of histopathologic and electron microscopic determinants of keratoacanthoma and squamous cell carcinoma

Abstract: Histopathologic study of 108 keratoacanthomas and 14 squamous cell carcinomas failed to reveal any consistent, single feature allowing for their distinction. Variation in clinical features of keratoacanthoma minimizes their value in this regard. On the other hand, crater, flask‐like configuration, lipping of edges, collarette and cytoplasmic eosinophilia were statistically more frequent in lesions regarded as keratoacanthoma whereas atypical cytologic alterations including greater numbers of typical and atypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 17 publications
2
30
1
Order By: Relevance
“…The Dsg staining that we have found appears consistent with the results of electron microscopical studies in KAs, in which the numbers and cell-surface densities of desmosomes have been found to be normal whereas in SCCs they are reduced (Fisher et al, 1972;Miracco et al, 1992). We are not aware of any ultrastructural studies of desmosomes in AKs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Dsg staining that we have found appears consistent with the results of electron microscopical studies in KAs, in which the numbers and cell-surface densities of desmosomes have been found to be normal whereas in SCCs they are reduced (Fisher et al, 1972;Miracco et al, 1992). We are not aware of any ultrastructural studies of desmosomes in AKs.…”
Section: Discussionsupporting
confidence: 89%
“…We have examined the staining for Dsg using the monoclonal antibody 33-3D, a mouse IgM monoclonal antibody, that recognizes the cytoplasmic domains of human Dsgl and Dsg2 and can be used on frozen sections (Vilela et al, 1995; DR Garrod, unpublished observations (Fisher et al, 1972;Janecka et al, 1978;Schwartz, 1994;Schwartz, 1996).…”
mentioning
confidence: 99%
“…Histopathologic diagnosis was rendered as KA, SCC, or undetermined. Elastic fibers were not evaluated because, despite the fact that it has been demonstrated that the presence of intraepithelial elastic fibers favors the diagnosis of KA, [8][9][10][11][12][13][14][15] this finding is not reliable for differentiating between the two tumors. 4 Initially, the variables were evaluated descriptively.…”
Section: Methodsmentioning
confidence: 99%
“…In relatively well differentiated areas of human tumours they found several gap junctions, but none in poorly differentiated areas. The numerical decrease of desmosomes and appearance of desmosome-free cytoplasmic processes has been described not only in squamous tumours, but also in pre-malignant lesions of the epithelium (Klingmuller et al, 1970;Fisher et al, 1972;Sugar, 1972;Lever & Schaumburg-Lever, 1975;Schindler et al, 1982). In the developing invasive character of tumours, McNutt (1976) suggested that the decreased number of hemidesmosomes may play a significant role.…”
Section: Discussionmentioning
confidence: 99%